Female cancer awareness and screening: evaluation from tertiary hospital in Eastern India - Ray, Payal Banerjee; Ray, Amitabh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Cancer awareness and emphasis on preventive oncology is an essential weapon in our war against cancer. Globally the approach towards cancer awareness is non-targeted with mass media and social media coverage being unselective. This study aimed to demonstrate the disparities prevalent in society especially in a developing country with regard to cancer awareness for two of the commonest female cancers and suggested measures to increase the efficacy of awareness programs in the urban and suburban population of a typical third world Indian metropolitan city. Methods: In a cross-sectional study conducted between January 2021 to June 2021, 119 suitable female patients attending the gynaecology OPD of a medical college and hospital were randomly selected. Informed consent was taken and their knowledge/awareness about preventive oncology in carcinoma breast and carcinoma cervix (two most common cancers in Indian women) was documented using pre tested and pre structured questionnaire. The results were analysed by suitable statistical tests. Results: Higher education and socio-economic condition was associated with increased levels of awareness for preventive measures of carcinoma breast and carcinoma cervix. Within each educational strata, higher socio-economic status predicted for increased awareness for risk factors, screening tests and vaccination. Conclusions: Subtle differences in the patterns and degree of awareness in common female cancers were noticed with regard to educational and socio-economic standards in the studies population. These have widespread implications in planning awareness programs in resource constrained setting to ensure most efficacious utilization of Cancer awareness and Prevention programmes.